Digital Transformation In Public Services: A Legal Review Of SPBE In Indonesia - Sipayung, Etla Elva; Jamaludin; Padilah, Hani Patul (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study examines the implementation Electronic Based Government Systems (SPBE) in Indonesia, focusing on legal aspects. It analyzes the regulatory framework, challenges, and the impact of digital transparency, legal materials. Findings indicate the while SPBE enhances servive efficiency and transparency, legal challenges persist in data protection and inter agency coordination.